2019
DOI: 10.1111/aor.13397
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term outcomes of intra‐aortic balloon pump combined with venoarterial extracorporeal membrane oxygenation: A systematic review and meta‐analysis

Abstract: The effectiveness of intra‐aortic balloon pump (IABP) combined with venoarterial extracorporeal membrane oxygenation (VA‐ECMO) in patients with cardiogenic shock or cardiac arrest remains controversial. The aim of this systematic review and meta‐analysis was to investigate the short‐term clinical outcomes of IABP combined with VA‐ECMO versus VA‐ECMO alone. We searched PubMed, Embase, and the Cochrane Library for English language articles published from inception to August 18, 2018. Observational studies compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…In a recent meta-analysis, Wang et al found that an IABP could improve the success rate of weaning from VA-ECMO but did not reduce in-hospital mortality. 9 Others percutaneous techniques include atrial septostomy, atrial stenting, cannulation of the LV via a percutaneous pigtail stent, or the combination of a miniature axial blood pump associated with VA-ECMO. 2 In a recent multicenter, retrospective cohort study, this combination was found to be associated with a significantly lower in-hospital mortality rate, relative to treatment with VA-ECMO alone.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, Wang et al found that an IABP could improve the success rate of weaning from VA-ECMO but did not reduce in-hospital mortality. 9 Others percutaneous techniques include atrial septostomy, atrial stenting, cannulation of the LV via a percutaneous pigtail stent, or the combination of a miniature axial blood pump associated with VA-ECMO. 2 In a recent multicenter, retrospective cohort study, this combination was found to be associated with a significantly lower in-hospital mortality rate, relative to treatment with VA-ECMO alone.…”
Section: Discussionmentioning
confidence: 99%
“…IABP is frequently used in cardiogenic shock to improve diastolic coronary perfusion, as well as reduce left ventricular afterload and pulmonary edema. When used together with VA-ECMO it may improve coronary and cerebral perfusion, [68][69][70][71] facilitate left ventricular unloading and weaning from VA-ECMO, 72 reduce hospital mortality, 73 and reduce the risk of pulmonary edema 74 .…”
Section: Iabpmentioning
confidence: 99%
“…Wang et al 72 conducted a systematic review and meta-analysis of 12 observational studies including 3,704 patients supported with VA-ECMO with or without an IABP for cardiogenic shock or cardiac arrest. A greater proportion of patients in the VA-ECMO + IABP group were successfully weaned from VA-ECMO, compared with patients who received VA-ECMO without an IABP (77.9% v 61.2%; RR 1.28; 95% CI 1.21-1.35).…”
Section: Iabpmentioning
confidence: 99%
“…Li Wang and Zhen Xing of The First Affiliated Hospital of Hebei North College, Hebei, People’s Republic of China studied the effectiveness of IABP combined with venoarterial extracorporeal membrane oxygenation (VA‐ECMO) in patients with cardiogenic shock or cardiac arrest by a systemic review and meta‐analysis to investigate the short‐term clinical outcomes of IABP combined with VA‐ECMO versus VA‐ECMO alone. They searched PubMed, Embase and the Cochrane Library for English language articles published from inception to August 18, 2018.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%